Incorporation of Methanol into Pectic Substance - Roberts, R. M. (1967)
Others have shown that l-methionine is utilized in the biosynthesis of methyl ester groups in pectic substance. Methanol, like l-methionine, is used for methyl ester biosynthesis by detached parsley leaves (Petroselinum crispum). When a combination of methanol-(3)H and methanol-(14)C is given to parsley leaves, methanol recovered from pectic substance by alkaline hydrolysis has a (3)H/(14)C ratio about one-fourth that of the mixture administered. Unlike l-methionine, methanol is oxidized prior to its utilization as a carbon source for methyl ester biosynthesis. Parsley leaves given methyl d-galacturonate-methyl-(14)C also form pectic substance in which methyl groups are labeled but incorporation appears to proceed by way of methanol metabolism after hydrolysis of methyl d-galacturonate.